The Impact of the Implementation of the International Baccalaureate (IB) Curriculum on Shaping the Quality of Teacher Performance at Islamic Village Tangerang School - Nada Shofa Lubis; M. Syadeli Hanafi; Sholeh Hidayat (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
The International Baccalaureate (IB) curriculum has emerged as a preferred global education framework in many schools worldwide. It not only emphasizes academic achievement but also fosters essential skills for success in an increasingly interconnected global society. This study aims to analyze the impact of implementing the IB curriculum on the quality of teacher performance. Employing a mixed-methods approach with a qualitative focus supported by quantitative data, the study involved 58 teachers from Islamic Village schools: 17 kindergarten, 29 elementary, 6 junior high, and 6 senior high school teachers, with no age restrictions. Data were collected through questionnaires and document analysis, and analyzed using descriptive qualitative methods. The findings indicate that the implementation of the IB curriculum significantly enhances various aspects of teacher performance: teaching ability (88.90%), understanding of subject matter (90.62%), student interaction (89.74%), classroom management (90.07%)—all rated as "very good." Meanwhile, professional development (78.88%) and contribution to student growth (78.59%) were categorized as "good." Overall, the IB curriculum has positively influenced teacher performance at Islamic Village Schools across all education levels. This study contributes to the enhancement of teacher professional competence and supports the cultivation of a strong school culture and professionalism.